2020
DOI: 10.3390/jcm9124004
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Mfa1 Induces Chemokine and Cell Adhesion Molecules in Mouse Gingival Fibroblasts via Toll-Like Receptors

Abstract: Porphyromonas gingivalis Mfa1 fimbriae are thought to act as adhesion factors and to direct periodontal tissue destruction but their immunomodulatory actions are poorly understood. Here, we investigated the effect of Mfa1 stimulation on the immune and metabolic mechanisms of gingival fibroblasts from periodontal connective tissue. We also determined the role of Toll-like receptor (TLR) 2 and TLR4 in Mfa1 recognition. Mfa1 increased the expression of genes encoding chemokine (C-X-C motif) ligand (CXCL) 1, CXCL3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…These structures participate in auto-aggregation and biofilm formation, and their assembly and structure are similar to the major fimbriae (48). Further, the main subunit, Mfa1, which is not expressed in the W83 strain (43), has been shown to activate fibroblasts in a partially TLR2-dependent manner (26,49). This raises the possibility that not only major fimbriae components, but also minor fimbriae could undergo modification by PPAD which modulates their TLR2-stimulating potential.…”
Section: Discussionmentioning
confidence: 99%
“…These structures participate in auto-aggregation and biofilm formation, and their assembly and structure are similar to the major fimbriae (48). Further, the main subunit, Mfa1, which is not expressed in the W83 strain (43), has been shown to activate fibroblasts in a partially TLR2-dependent manner (26,49). This raises the possibility that not only major fimbriae components, but also minor fimbriae could undergo modification by PPAD which modulates their TLR2-stimulating potential.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of Mfa1, the recognition receptor remains controversial. We recently reported that TLR4 is mainly important for the recognition of Mfa1 by gingival fibroblasts [ 17 ]. Takahashi et al reported that TLR2 may be important for Mfa1 recognition by bronchial epithelial cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, TLR2 is important for P. gingivalis to produce proinflammatory cytokines [ 15 , 16 ]. It has been suggested that TLR2 and TLR4 may be involved in the recognition of P. gingivalis fimbriae [ 17 , 18 ], but a consensus has not been reached so far.…”
Section: Introductionmentioning
confidence: 99%
“…Hamada et al reported that purified Mfa1 fimbriae upregulated proinflammatory cytokines, such as IL-1α, IL-β, IL-6, and TNFα, via the TLR2 and CD14 pathways in human monocytes and murine peritoneal macrophages [ 45 , 121 ]. A recent study indicated that recognition by TLR2 and TLR4 was involved in the immunomodulatory actions of purified Mfa1 fimbriae and contributes to the overall action of gingival fibroblasts [ 122 ].…”
Section: Functions Of Fima and Mfa1 Fimbriaementioning
confidence: 99%
“…Therefore, the latter phenotype may not be a direct consequence of accessory protein loss. Our research group recently compared immunomodulation induction by Mfa1 fimbriae purified from the wild type and the mfa5 -deficient mutant lacking the Mfa3–5 tip structure [ 122 ]. The mfa5 mutant presented with relatively upregulated immunomodulatory genes.…”
Section: Functions Of Fima and Mfa1 Fimbriaementioning
confidence: 99%